Enhancing usability in CITIDEL: multimodal, multilingual, and interactive visualization interfaces - Perugini, Saverio; McDevitt, Kathleen; Richardson, Ryan; Pérez-Quiñones, Manuel A.; Shen, Rao; Ramakrishnan, Naren; Williams, Chris; Fox, Edward A. (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
We describe four usability-enhancing interfaces to CITIDEL aimed at improving the user experience and supporting personalized information access by targeted communities. These comprise: a multimodal interaction facility with capability for out-of-turn input, interactive visualizations for exploratory analysis, a translation center exposing multilingual interfaces, as well as traditional usability enhancements. Pilot studies demonstrate the resulting improvements in quality, as measured across a number of metrics.